From nascent to actual entrepreneurship: the effect of entry barriers - André J. van Stel; A. Roy Thurik; David J. Storey; Sander Wennekers (Max Planck Institute of Economics, 2005)
This exploratory study focuses on the conversion from nascent to actual entrepreneurship and the role of entry barriers in this process. Using data for a sample of countries partici-pating in the Global Entrepreneurship Monitor between 2002 and 2004, we estimate a two-equation model explaining the nascent entrepreneurship rate and the young business entre-preneurship rate, while taking into account the interrelationship between the two variables (i.e. the conversion). Furthermore various determinants of entrepreneurship reflecting the demand and supply side of entrepreneurship as well as government intervention are incor-porated in the model. We find evidence for a strong conversion effect from nascent to ac-tual entrepreneurship. We also find positive effects on entrepreneurial activity rates of la-bour flexibility and tertiary enrollment and a negative effect of social security expenditure. Concerning the effect of entry regulations we find mixed results. Using one set of entry regulation measures we find no effects whereas using data from a second source we find a weak negative effect of more burdensome entry regulations on the rate of entrepreneurship.
Keywords: H10; M13; 330; nascent entrepreneurship; young businesses; entry regulations